ANALISIS PERHITUNGAN PENYUSUTAN ASET TETAP BERDASARKAN STANDAR AKUNTANSI PEMERINTAH ( PP.NO.71 TAHUN 2010) PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN BERAU - Rima Restu Wulandari Swadi; Siti Munawaroh; Suryadi Suryadi (Jurnal Ekonomi STIEP, 2022)
The purpose of this study was to determine the calculation of depreciation of fixed assets based on government accounting standards (PP No. 71 of 2010) at the Regional Financial and Asset Management Agency of Berau Regency. In this study, the author focuses on 3 Fixed Assets, namely Film Screens/Projectors, Other Two-Wheeled Motorized Vehicles and PC Units. The analytical tool used is one of the differentiating methods in accordance with PP NO. 71 of 2010, namely: the straight line method. The results of this study indicate that the Regional Financial and Asset Management Agency of Berau Regency in presenting its financial statements related to the calculation of assets that have been in accordance with Government Accounting Standards (PP. No. 71 of 2010) and does not conflict with this regulation. The Regional Financial and Asset Management Agency of Berau Regency uses the straight-line method to calculate its fixed assets.